The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6943022
|View full text |Cite
|
Sign up to set email alerts
|

A novel user-guided interface for robot search

Abstract: Abstract-Human operators play a key role in robotic exploration and search missions, as the interpretation of camera images typically requires the visual perception skills of humans. Thus one the key challenges in building effective robotic systems for such missions lies in developing good operator interfaces. In this paper, we present a novel asynchronous user-guided interface for human operators of robotic search of an unknown area. Enabled by efficient methods to store and retrieve recorded images (and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, the communication lags and limited human attention make it difficult for human operators to simultaneously inspect 4∼12 live video streams and use these to make decisions such as finding victims or directing the robots' motion. To alleviate these issues, an asynchronous interface was proposed, which shows the priority image or point of interest (POI) to the operator [21]. The experiments demonstrated that with the asynchronous interface the operator can reduce victims' marking errors [22].…”
Section: B Human-robot Interface For Spatial Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the communication lags and limited human attention make it difficult for human operators to simultaneously inspect 4∼12 live video streams and use these to make decisions such as finding victims or directing the robots' motion. To alleviate these issues, an asynchronous interface was proposed, which shows the priority image or point of interest (POI) to the operator [21]. The experiments demonstrated that with the asynchronous interface the operator can reduce victims' marking errors [22].…”
Section: B Human-robot Interface For Spatial Searchmentioning
confidence: 99%
“…For example, in [20], [21], the robots' paths are planned by algorithms, and the images' priority is decided based on the uncovered area. In other words, the objective function of the priority images is submodular.…”
Section: B Subgoal Assistance For Human-robot Interactionmentioning
confidence: 99%
“…This meant that an operator was still required to watch all imagery taken by all the robots. Kosti, Kaminka, and Sarne (2014) developed a novel user interface that allowed the user to view images in context of their location on the map, automatically selecting the best image showing a given location.…”
Section: The Latest Israeli Ai Achievementsmentioning
confidence: 99%
“…Much research has focused on improving the operator's control, suggesting various synchronous and asynchronous interfaces for operating the robots and managing the task (Wang et al 2011;Kosti, Sarne, and Kaminka 2014). Still, not all human operators possess the same level of expertise, and the effectiveness of their navigation can highly vary (McGinn, Sena, and Kelly 2017).…”
Section: Introductionmentioning
confidence: 99%